Electric Double Layer: A Desolvated Solid–Solid Interface for a High‐Capacitance Electric Double Layer (Adv. Energy Mater. 12/2019). Issue 12 (26th March 2019) - Wang, Yu‐Zuo; Shan, Xu‐Yi; Ma, Li‐Po; Wang, Jia‐Wei; Wang, Da‐Wei; Peng, Zhang‐Quan; Cheng, Hui‐Ming; Li, Feng
Abstract : In the article number1803715 Da‐Wei Wang, Feng Li, and co‐workers design a novel electric double layer inside a solid‐solid interface. The solid‐solid interface is composed of an electrode and a solid electrolyte interface layer, which supply a de‐solvated environment for establishment of electric double layer and can lead to a capacitance‐increase effect.